Traditional herbal medicine for hyperuricemia: A review of randomized clinical trials - Arief Gunawan Darmanto; Florence Pribadi; Yoselyn Sucahyo; Arini Wiraputri; Della Mardhika; Christ Tambuang; Adinda Setiawan; Ummu Habibah; Kevin Luke (Sains Medika, 2023)
In the last decades, traditional herbal medicine for gout has been rapidly advanced. Numerous herbs have been identified for their hypouricidal effect. This review aims to explain the potential and mechanisms of traditional herbal medicine in reducing serum uric acid (sUA). This review included five RCTs and four traditional herbal medicine formulas from a previous systematic review. Articles published in non-English language were excluded for further analysis. Despite limited RCTs design, the formula of Chuanhu; Tufu, and ZinutriK® were beneficial for hyperuricemic individuals. While Yellow-dragon Wonderful-seed mixture showed limited hypouricemic feature. Based on these findings, traditional herbal medicine holds promising potential in treating hyperuricemia and gout. However, further studies are required.